2015
DOI: 10.3126/jsan.v1i2.13576
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic management for laparoscopic cholecystectomy in a child

Abstract: Laparoscopic surgical techniques offer several advantages over conventional open surgery. However, anaesthesia for laparoscopic surgical procedures is challenging due to various associated physiological consequences mainly of intra-peritoneal carbon dioxide insufflation and positioning. Gall stone disease is rare in pediatric age group and therefore, experience of anaesthetic management in such a condition is limited. Here we describe anaesthetic management of a 56-month-old male child scheduled for laparoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It has been observed that ultrasound-guided ESPB (US-ESPB) can alleviate both localized and systemic pain [14,15]. Many operations on the abdomen and genital regions of children of all ages are now routinely performed using laparoscopic techniques [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that ultrasound-guided ESPB (US-ESPB) can alleviate both localized and systemic pain [14,15]. Many operations on the abdomen and genital regions of children of all ages are now routinely performed using laparoscopic techniques [16].…”
Section: Introductionmentioning
confidence: 99%